Determination of threshold pore water pressure coefficient (Ru threshold) for landslide prediction - Cajucom, Alarice Ia F.; Misola, Ryan B.
Landslides are geotechnical hazards prevalent in the country, putting several communities in danger and causing heavy damage in its wake. A common type of landslide is rainfall-induced shallow landslides. Current slope stability methods either rely on factor of safety method or finite element computer simulation - which require several soil hydraulic properties, long processing time and costly software. The numerous inputs, complex processes and high cost hinder the general public from self-assessing the stability of slopes near them - leaving them to depend on limited and highly generalized hazard maps, if there are any. This leaves the general public vulnerable to this geotechnical hazard. On the other hand, the pore water pressure coefficient threshold value method, Ru threshold is a simple slope stability method widely used before for saturated soils. However, it became obsolete with the development of unsaturated soil mechanics, especially since most shallow landslides occur on unsaturated soils. In determining the Ru threshold values, Hydrus-1D, a free software, was used to model and simulate seepage through soil. The pore water pressure, moisture content, soil unit weight, and other properties from seepage analysis were used to compute for the transient Ru values of the soil. Factor of safety formula on infinite slopes was then used to determine slope stability - the results of which were ensured to follow expected trends. After verifying the correctness of the factor of safety formula, a Ru threshold formula was developed by modifying the factor of safety formula. It was found out that only the soil type and slope angle hugely affected the Ru threshold values. Slope stability was then predicted for the depths and times were the soil's Ru exceeded the computed Ru threshold values. To verify the validity of the computed Ru threshold values, they were compared to the Ru at predicted failure time and depth (Ru failure) in the factor of safety method. All Ru failure values exceeded the Ru threshold values - indicating landslide occurrence since the threshold value was exceeded. Also, slope stability predictions using the factor of safety method and Ru threshold method were compared. Predictions on landslide occurrence, failure time and failure depth for cohesionless soils (sand and silt) were similar for both methods. However, a more conservative prediction as derived from Ru threshold method for clayey soils since Ru does not consider cohesion. The similarity in the prediction of both methods verifies the correctness of the Ru threshold values computed in the study. As a practical application, rapid slope stability assessment for more rainfall intensity combinations was done using threshold pore water pressures computed using Ru threshold values. Lastly, a self-check assessment table which indicates landslide occurrence, time and depth at the different rainfall intensity combinations was successfully developed. With this, the study proved that the updated Ru threshold method for unsaturated soils can produce a free, simple, rapid and accurate preliminary slope stability prediction method that is useful to the general public.